Spectrophotometric Multicomponent Resolution of a Tablet Formulation Containing Lisinopril and Hydrochlorothiazide by Multivariate Calibration Methods - Dinç, Sule; Aksu Dönmez, Özlem; Asçi , Bürge; E. Bozdogan, Abdürrezzak (Asian Journal of Chemistry, 2012)
Partial least squares (PLS), principal components regression (PCR) and multiple linear regression (MLR) methods were used for the determination of lisinopril (LIS) and hydrochlorothiazide in a pharmaceutical formulation. Experimental calibration matrix was constructed using 25 samples, according to multilevel multifactor design.The concentration ranges considered were 4-20 μg mL-1 for lisinopril and 3-11 μg mL-1 for hydrochlorothiazide. The absorbances were recorded between 190 and 400 nm every 1 nm. The validation of the multivariate methods was realized by analyzing the synthetic mixtures of lisinopril and hydrochlorothiazide. These multivariate methods were also applied to the commercial tablet formulations containing lisinopril and hydrochlorothiazide. High performance liquid chromato-graphy method was used as a comparison method. The results obtained were statistically compared with each other.